Youth participation in development programmes in Mogale City local municipality - Mbanjwa, Zamile Patricia (My University, 2015)
Mogale City Local Municipality youth consists of more than 30% of the population, and it participates in both social and economical activities. The Office of the Executive Mayor in Mogale City Local Municipality regards participation of youth in development programmes as a significant focus for social development programmes. This thesis has attempted to assess the contributing factors to low levels of youth participation in Mogale City Local Municipality. The study argues that contributing factors such as inadequate participation of youth in the development programmes, youth pull and push participation factors, development programmes significance, youth mentorship and return on investment have lessened the desire of youth to participation in development programmes. Subsequently, a qualitative technique was utilised by the researcher. A survey of literature review and semi-structured interviews were carried out to formulate comprehensive and harmonious solutions that redress the shortcomings facing the Mogale City Local Municipality to enhance youth participation in development programmes. The argument of this study is that the youth should be partners in the designing of policies, systems, strategies and policies that permit the participation of the youth in development programmes in Mogale City Local Municipality. The key finding is that there is a disconnection between Mogale City Local Municipality development programmes and what the youth needs. This affects the level of youth participation and impacts negatively on its interests and well-being. The study concludes by suggesting remedial mechanisms relevant to this case.
MM
Keywords: Youth -- Government policy,Youth development,Public administration -- South Africa.